2021
DOI: 10.2147/dmso.s321756
|View full text |Cite
|
Sign up to set email alerts
|

Poor Glycemic Control and Its Contributing Factors Among Type 2 Diabetes Patients at Adama Hospital Medical College in East Ethiopia

Abstract: Background:Poor glycemic control is a major public health issue among patients with type 2 diabetes mellitus and a significant risk factor for the progression of diabetic complications. This study aimed to assess the magnitude and contributing factors of poor glycemic control among type 2 diabetes patients on follow-up at Adama Hospital Medical College (AHMC) in East Ethiopia. Methods: A cross-sectional study was conducted among 245 type 2 diabetes patients on follow-up at AHMC from March 1 to 30, 2020. All ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 31 publications
8
34
1
1
Order By: Relevance
“…The current study discovered that diabetic patients who chewed Khat and smoked were more likely to have poor self-care for their diabetes. Our findings were consistent with previous studies [ 44 , 45 , 46 ]. There is a relationship between the habit of Khat chewing and the development of noninsulin-dependent diabetes mellitus, which may be explained by the adverse health effects of pesticide residues on Khat chewers.…”
Section: Discussionsupporting
confidence: 94%
“…The current study discovered that diabetic patients who chewed Khat and smoked were more likely to have poor self-care for their diabetes. Our findings were consistent with previous studies [ 44 , 45 , 46 ]. There is a relationship between the habit of Khat chewing and the development of noninsulin-dependent diabetes mellitus, which may be explained by the adverse health effects of pesticide residues on Khat chewers.…”
Section: Discussionsupporting
confidence: 94%
“…The proportion of good glycemic control was comparable to the results reported in the Dilchora Referral Hospital, Ambo, Brazil, Iran, and Jordan 5 , 12 15 . In other studies, approved in Adama Medical College Hospital (35.9%), Ethiopia (31.1%), Referral Hospitals of Amhara Region (44.7%), Riyadh (32.3%), Al-Hasa (32.1%), Jazan (26%), Oman (35%), United Arab Emirates (31%), Kuwait (21.2%) and Rawalpindi (24%), good glycemic control was inferior unlike the current study 6 8 , 16 – 21 . The observed difference between this and other studies could be because of the difference in sample size, study design (this study used longitudinal data, while other studies used cross-sectional data), and the operational definition used (this study uses fasting blood glucose levels to categorize glycemic control, while other studies use hemoglobin A1c to categorize glycemic control).…”
Section: Discussioncontrasting
confidence: 73%
“…Patients whose weights were 78–87 kg had lower odds of good glycemic control compared to those patients whose weights were 58–69 kg. This finding was supported by previous studies 6 8 , 30 and contradicts the study conducted in Ethiopia, which reported no significant association between the weight of patients with poor glycemic control 5 , 9 . The possible justification is that higher weight will increase blood sugar and increase the risk of diabetes complications.…”
Section: Discussionsupporting
confidence: 55%
“…Until now, previous studies have not assessed the influence of SBP and DBP on the progression of FBS [ 9 , 18 – 20 ]. Besides, most of the studies on the associated factors of FBS among T2DM were cross-sectional in Ethiopia [ 6 , 21 24 ].…”
Section: Introductionmentioning
confidence: 99%